2023
DOI: 10.1177/14644207231196266
|View full text |Cite
|
Sign up to set email alerts
|

Using shot peening and burnishing to improve fatigue performance of additively manufactured 316L stainless steel

Daniyal Sayadi,
Hossein Rangrizian,
Alireza Khodabandeh
et al.

Abstract: Despite the growing demands for personalized items, the capacity of conventional production techniques is restricted to respond to such needs. Instead of conventional manufacturing processes, the intended structure can be directly constructed in a layer-by-layer manner, also known as additive manufacturing (AM). Among AM methods, selective laser melting (SLM) has gained a great deal of attention due to its low cost and availability. However, the poor surface quality in this method is still a problem as it may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…They revealed that the final surface roughness of post-processed samples depends on the surface roughness of the as-built material. Sayyadi et al [7] revealed that burnishing can be used as a final post-treatment operation after selective laser melting and shot peening to enhance the fatigue life of stainless steel 316. They confirmed that the sequence of shot peening-burnishing yields better roughness compared to solely shot peening or burnishing.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the final surface roughness of post-processed samples depends on the surface roughness of the as-built material. Sayyadi et al [7] revealed that burnishing can be used as a final post-treatment operation after selective laser melting and shot peening to enhance the fatigue life of stainless steel 316. They confirmed that the sequence of shot peening-burnishing yields better roughness compared to solely shot peening or burnishing.…”
Section: Introductionmentioning
confidence: 99%